HEAVY METALS IN THE ENVIRONMENT OF VANPHONG - BENGOI BAY IN KHANH HOA PROVINCE - Vinh, Le Thi (Vietnam Journal of Marine Science and Technology, 2012)
The paper represents some aspects on the heavy metals in water, sediment, oyster Saccostrea cucullata and seagrass (Thalassia hemprichii and Enhalus acoroides) at Vanphong - Bengoi bay. Results of surveys (performed in April - June 2009, dry season, and October - November 2009, rainy season) show that the heavy metal concentrations in water (Zn from 8.7 to 34.0mg/l; Cu from 0.6 to 42mg/l; Pb from 0.4 to 3.8mg/l; Cd from 0.04 to 0.32mg/l and Cr from 1.1 to 3.1mg/l) were not high. In sediment, heavy metal contents (Zn from 19.4 to 68.2mg/g; Cu from 0.4 to 11.7mg/g; Pb from 1.9 to 22.9mg/g; Cd from 0.5 to 0.21mg/g and Cr from 4.3 to 26.6mg/g) were also not high compared to critical values in criteria for Aquatic Life Protection except sediment near Huyndai Vinashin-Shipyard (HVS). In oysters, heavy metal contents (Cu from 100 to 246 mg/g wet weigh; Pb from 0.19 to 0.44mg/g wet weigh; Cd from 0.4 to 0.83mg/g wet weigh and Cr from 0.28 to 1.03mg/g wet weigh) were comparatively low compared to the maximum permissible levels for seafood safety, except Cu, especially in My Giang - near HVS. Seagrass leafs also considerably accumulated heavy metals (Fe from 54.3 to 68.2mg/g dry weigh; Zn from 29.6 to 35.3mg/g weigh; Cu from 5.0 to 5.4mg/g weigh and Pb from 1.8 to 2.6mg/g weigh).The data also indicated that there were no difference in heavy metal levels in water and oyster between two seasons.